Effect of acidity, basicity and ZrO2 phases of Cu-Ni/ZrO2 catalysts on the direct synthesis of diethyl carbonate from CO2 and ethanol (2016)
Cu-Ni/ZrO2 catalysts with different Cu:Ni molar ratios were synthesized and tested in the direct synthesis of diethyl carbonate from carbon dioxide and ethanol. The effect of Cu:Ni molar ratio on the acidity and basicity of the catalysts was investigated using NH3 and CO2-TPD, respectively. Experimental results revealed that Cu:Ni-3:1/ZrO2 and Cu:Ni-2:1/ZrO2 samples exhibited the largest acidity and basicity, as well as the highest yield to diethyl carbonate. Additionally, XRD and Raman studies showed that structural and crystalline properties of Cu:Ni-3:1/ZrO2 and Cu:Ni-2:1/ZrO2 were modified with the incorporation of Cu and Ni into ZrO2 which were related to the improved catalytic activity in comparison to Cu:Ni-1:1/ZrO2, Cu:Ni-1:2/ZrO2, Cu:Ni-1:3/ZrO2 and ZrO2 materials.